2011
DOI: 10.1371/journal.pcbi.1001042
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Stability of Histone H3 Is a Necessary but not Sufficient Driving Force for its Evolutionary Conservation

Abstract: Determining the forces that conserve amino acid positions in proteins across species is a fundamental pursuit of molecular evolution. Evolutionary conservation is driven by either a protein's function or its thermodynamic stability. Highly conserved histone proteins offer a platform to evaluate these driving forces. While the conservation of histone H3 and H4 “tail” domains and surface residues are driven by functional importance, the driving force behind the conservation of buried histone residues has not bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…As asymmetrical modifications have previously been reported on histone H3 in vivo ( Voigt et al, 2012 ), we began by examining H3. Previous structural work revealed that two molecules of histone H3 interact through their carboxy-terminal four-helix bundle to form a homodimer ( Luger et al, 1997 ; Ramachandran et al, 2011 ; White et al, 2001 ) ( Figure 1A ). We performed site-directed mutagenesis on the Ala110, Ala114 and Leu130 residues of the HHT1 gene.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As asymmetrical modifications have previously been reported on histone H3 in vivo ( Voigt et al, 2012 ), we began by examining H3. Previous structural work revealed that two molecules of histone H3 interact through their carboxy-terminal four-helix bundle to form a homodimer ( Luger et al, 1997 ; Ramachandran et al, 2011 ; White et al, 2001 ) ( Figure 1A ). We performed site-directed mutagenesis on the Ala110, Ala114 and Leu130 residues of the HHT1 gene.…”
Section: Resultsmentioning
confidence: 99%
“…We performed site-directed mutagenesis on the Ala110, Ala114 and Leu130 residues of the HHT1 gene. These residues were chosen because they were spatially close and within the bundle region that interacts to form the H3 homodimer ( Luger et al, 1997 ; Ramachandran et al, 2011 ; White et al, 2001 ). These neutral amino acids were mutated to acidic or basic residues to make them electronegative or electropositive under physiological conditions.…”
Section: Resultsmentioning
confidence: 99%
“…To test this proposition, we designed a mutant H3.3 that could interact with DAXX, but could not be stably deposited into nucleosomes. A previous study investigated the effects of amino acid substitutions in H3 on the thermodynamic stability of the H3–H3ʹ interface within the symmetric (H3–H4) 2 tetramer—an essential intermediate toward nucleosome formation 36 . The authors found that substitutions at positions L126 and L130 in yeast H3 led to disruption of hydrophobic interactions with the adjacent H3 molecule within the same nucleosome.…”
Section: Resultsmentioning
confidence: 99%
“…We now demonstrate that DAXX mediates H3.3 recruitment to PML bodies independently of ATRX. Our findings of faster PML targeting of a mutant of H3.3 (H3.3[H113A]) that has computationally been found to abolish the formation of (H3.3-H4) 2 tetramers (Ramachandran et al 2011) suggest a model in which DAXX recruits (H3.3-H4) dimers rather 3-H4) dimer recruitment to PML bodies prior to chromatin deposition. In pathway 1, DAXX recruits the (H3.3-H4) dimer to PML bodies.…”
Section: Daxx Targets (H33-h4) Dimers To Pml Bodiesmentioning
confidence: 89%
“…3A) raises the question of whether this recruitment occurs in the form of (H3-H4) dimers or (H3-H4) 2 tetramers. To distinguish between these alternatives, we generated an H3.3 mutant in which His113 substitution with Ala (H3.3[H113A]) allows, in silico, H3-H4 dimerization but prevents the formation of stable (H3-H4) 2 tetramers by disrupting the H3-H39 hydrogen bond (Ramachandran et al 2011). H3.3(H113A)-mC colocalizes at foci with PML 24 h after transfection (Fig.…”
Section: Daxx Preferentially Targets H33-h4 To Pml Bodies As Dimers mentioning
confidence: 99%